2003
DOI: 10.3168/jds.s0022-0302(03)73690-x
|View full text |Cite
|
Sign up to set email alerts
|

Low-Fat Set Yogurt Made from Milk Subjected to Combinations of High Hydrostatic Pressure and Thermal Processing

Abstract: The combined use of high hydrostatic pressure (300 to 676 MPa, 5 min) and thermal treatment (85 degrees C, 30 min) in milk for the manufacture of low-fat yogurt was studied. The objective was to reduce syneresis and improve the rheological properties of yogurt, reducing the need for thickeners and stabilizers. The use of high hydrostatic pressure alone, or after thermal treatment, reduced the lightness and increased the viscosity of skim milk. However, milk recovered its initial lightness and viscosity when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(99 citation statements)
references
References 17 publications
7
89
1
2
Order By: Relevance
“…Similar tendency was established by Naik et al (2013) in skimmed milk after treatment at 250-450 MPa, significant decrease in the L* value was observed, and in ewe`s milk, by Gervilla et al (2001). Also Harte et al (2003) reported that milk subjected to HP treatment and thermal treatment followed by HP, loses its white colour and turns yellowish. Johnston et al (1992) proposed that the decrease in L* value could have been mainly due to disintegration of casein micelles by pressure into small fragments and that might be a possible explanation for obtained results in our research.…”
Section: Instrumental Evaluation Of Coloursupporting
confidence: 57%
See 1 more Smart Citation
“…Similar tendency was established by Naik et al (2013) in skimmed milk after treatment at 250-450 MPa, significant decrease in the L* value was observed, and in ewe`s milk, by Gervilla et al (2001). Also Harte et al (2003) reported that milk subjected to HP treatment and thermal treatment followed by HP, loses its white colour and turns yellowish. Johnston et al (1992) proposed that the decrease in L* value could have been mainly due to disintegration of casein micelles by pressure into small fragments and that might be a possible explanation for obtained results in our research.…”
Section: Instrumental Evaluation Of Coloursupporting
confidence: 57%
“…Hunter Luminance value (L* value) of milk is generally used as a measure of whiteness (Harte et al, 2003). The results of colour CIE L*a*b* measurements of the milk samples are shown in Table 2.…”
Section: Instrumental Evaluation Of Colourmentioning
confidence: 99%
“…Acid gels, such as yogurt, obtained from HHP (400-500 MPa) homogenized milk showed increased yield stress, resistance to normal penetration, elastic modulus and reduced syneresis with decrease in whey holding capacity and retention of more than 20% whey after centrifugation [36,37]. Similarly, Needs et al [27] recorded lower values of fracture stress in set yoghurts made from pressure-treated milk (60 MPa for 15 min) compared to heat treated milk.…”
Section: Effects Of High-pressure Technology On the Functional Propermentioning
confidence: 98%
“…Acidification of yoghurt milk with GDL (glucono-δ-lactone) at 200 MPa for 20 min resulted in fine coagulum, homogeneous gel than that of heat treated milk [19,22,36].…”
Section: Effects Of High-pressure Technology On the Functional Propermentioning
confidence: 99%
See 1 more Smart Citation